2015
DOI: 10.1159/000435878
|View full text |Cite
|
Sign up to set email alerts
|

The Pudendal Nerve and Its Branches in Relation to Richter's Procedure

Abstract: Objective: Variations in the branching pattern of the pudendal nerve (PN) have been described in the literature. This study investigated these variations in order to comment on a safe area for the placement of a Richter's stitch. Methods: Richter's procedure was performed on nine unembalmed female cadavers and followed by dissection. PN dissections were done on another 20 embalmed female cadavers. Variations in the branching pattern of the PN were noted and the distance between the Richter's stitch placed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…En la parte posterior de la fosa isquiorrectal, inmediatamente después de pasar el ligamento sacroespinoso, el nervio da su primera rama: el nervio rectal inferior, que penetra la fascia interna del músculo obturador para distribuirse en su territorio anal. 17,23 Mahakkanukrauh et al encontraron que en el 21% de las veces el nervio rectal inferior se origina independientemente de la raíz de S4 sin hacer parte del tronco del nervio pudendo. 13 La rama perineal penetra medialmente la fascia interna del músculo obturador deslizándose hacia la base del diafragma urogenital donde se bifurca en sus ramas terminales superficial y profunda.…”
Section: Anatomía Del Nervio Pudendounclassified
“…En la parte posterior de la fosa isquiorrectal, inmediatamente después de pasar el ligamento sacroespinoso, el nervio da su primera rama: el nervio rectal inferior, que penetra la fascia interna del músculo obturador para distribuirse en su territorio anal. 17,23 Mahakkanukrauh et al encontraron que en el 21% de las veces el nervio rectal inferior se origina independientemente de la raíz de S4 sin hacer parte del tronco del nervio pudendo. 13 La rama perineal penetra medialmente la fascia interna del músculo obturador deslizándose hacia la base del diafragma urogenital donde se bifurca en sus ramas terminales superficial y profunda.…”
Section: Anatomía Del Nervio Pudendounclassified
“…In the posterior portion of the ischiorectal fossa, immediately after the sacrospinous ligament, the nerve branches for the first time, giving rise to the inferior rectal nerve, which penetrates the internal fascia of the obturator muscle in order to innervate its anal territory. 47,58 Mahakkanukrauh et al found that, in 21% of cases, the inferior rectal nerve arises independently from the root of S4 without being part of the pudendal trunk. 41 The perineal branch penetrates medially into the internal fascia of the obturator muscle, sliding towards the base of the urogenital diaphragm where it divides into its superficial and deep terminal branches.…”
Section: Pudendal Nerve Anatomymentioning
confidence: 99%